The ALPPS procedure as a novel “liver-first” approach in treating liver metastases of colon cancer: the first experience in Greek Cypriot area - Petrou, Athanasios (World J Surg Oncol, 2016)
BACKGROUND: Despite recent advances in multimodality and multidisciplinary treatment of colorectal liver metastases, many patients suffer from extensive bilobar disease, which prevents the performance of a single procedure due to an insufficient future liver remnant (FLR). We present a novel indication for associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) as a “liver-first” approach when inadequate FLR was faced preoperatively, in a patient with extensive bilobar liver metastatic disease of colon cancer origin. CASE PRESENTATION: A 51-year-old lady was referred to our center due to a stage IV colon cancer with extensive bilobar liver disease and synchronous colon obstruction. During the multidisciplinary tumor board, it was recommended to proceed first in a palliative loop colostomy (at the level of transverse colon) operation and afterwards to offer her palliative chemotherapy. After seven cycles of chemotherapy, the patient was re-evaluated by CT scans that revealed an excellent response (>30 %), but the metastatic liver disease was still considered inoperable. Moreover, with the completion of 12 cycles, the indicated restaging process showed further response. Subsequent to a thorough review by the multidisciplinary team, it was decided to proceed to the ALPPS procedure as a feasible means to perform extensive or bilobar liver resections, combined with a decreased risk of tumor progression in the interim. CONCLUSIONS: All in all, ALPPS can offer a feasible but surgically demanding liver-first approach with satisfactory short-term results in selected patients. Larger studies are mandatory to evaluate short- and long-term results of the procedure on survival, morbidity, and mortality.